2000
DOI: 10.1093/ndt/15.1.50
|View full text |Cite
|
Sign up to set email alerts
|

Intradialytic removal of protein-bound uraemic toxins: role of solute characteristics and of dialyser membrane

Abstract: Urea and creatinine are far more efficiently removed than the other compounds under study, except for hippuric acid. There are no striking differences between the HF membranes. Moreover, compared with the LF membrane these HF membranes do not appear to be superior in removing the studied compounds.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
190
0
3

Year Published

2005
2005
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 236 publications
(199 citation statements)
references
References 31 publications
3
190
0
3
Order By: Relevance
“…65,73,74 Dialysis treatment with protein-leaking membranes has been proposed and it offers a greater clearance of retention protein−bound solutes. Nevertheless, large amounts (2-6 g/4 hours of session) of albumin loss are a major concern 75 because hypoalbuminemia is associated with increased mortality in HD patients.…”
Section: -72mentioning
confidence: 99%
See 1 more Smart Citation
“…65,73,74 Dialysis treatment with protein-leaking membranes has been proposed and it offers a greater clearance of retention protein−bound solutes. Nevertheless, large amounts (2-6 g/4 hours of session) of albumin loss are a major concern 75 because hypoalbuminemia is associated with increased mortality in HD patients.…”
Section: -72mentioning
confidence: 99%
“…116,124 The circulating concentration of free (active) IS remains unchanged in uremic patients, 71 even though one-fifth to one-third of the total IS is removable by HD. 71,73,125 Notably, the free form of IS is undetectable in healthy subjects, 71 suggesting that the equilibrium state of IS-albumin binding is different between healthy persons and CKD patients. In HD patients, serum IS level is independently correlated with serum creatinine.…”
Section: Is Indoxyl Sulfate a Culprit Inmentioning
confidence: 99%
“…In fact, despite their relatively modest strength and low density, plant fibers have been found to be capable of producing fibrous composites with high-specific strength. [8][9][10][11][12][13][14][15][16][17] Cellulose acetate and cellulose triacetate (CTA) are extensively used in the preparation of hemodialysis and desalination membranes. 10 Acetate and triacetate fibers of cellulose have lower strength and abrasion resistance than most man-made fibers, so these are frequently used in combination with synthetic polymers.…”
Section: Introductionmentioning
confidence: 99%
“…10 Acetate and triacetate fibers of cellulose have lower strength and abrasion resistance than most man-made fibers, so these are frequently used in combination with synthetic polymers. [10][11][12][13][14][15] Furthermore, it has been found that among the cellulose esters, CTA has the highest thermal stability. 16 It is known to have better hydrolytic stability and greater resistance to reactions with free chlorine and biodegradation.…”
Section: Introductionmentioning
confidence: 99%
“…Clearance of middle molecules and protein-bound uremic solutes will require increases in blood and dialysate flow rates (17)(18)(19)(20)(21)(22). In an ideal scenario, we would know the identities of the molecular mediators of uremia and adjust dialysis settings to optimize their clearance.…”
mentioning
confidence: 99%